2010
DOI: 10.1177/1440783310365583
|View full text |Cite
|
Sign up to set email alerts
|

Enacting virtual connections between work and home

Abstract: The potential for information and communication technologies to reorganize time and space has emerged as a key theme in social theory. Affordances of the Internet mean that it has the capacity to affect temporal and spatial boundaries dividing work and home. Some theorists express concern that this may extend work into times normally reserved for family life, while others argue the Internet can encourage flexible work practices and result in better work—life balance. Focusing on a nationally representative sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 34 publications
7
70
0
3
Order By: Relevance
“…''Street culture'' has been changed into ''room culture'' (Bacigalupe, 2011;Mesch, 2006b), where adolescents are isolated in their rooms playing and communicating with friends (Cardoso et al, 2008). The pattern of ICTs use seems to vary between email (Padilla-Walker, Coyne Cardoso et al, 2008;Ferguson, 2013;Ferguson, San Miguel, Garza, & Jerabeck, 2012;Lenhart et al, 2008;Sherry et al, 2006) and cell phone (Padilla-Walker et al, 2012;Wajcman, Rose, Brown, & Bittman, 2010). However, more than identify the pattern of the ICTs used by youth, is important to understand the context in which they are used (e.g., room alone, in mobility) and the interactions (e.g., contact with strangers, game with their offline partners, text messages to parents regarding difficult subjects) that they form in order to understand adolescents (Bacigalupe & Camara, 2011): how they construct their identity, how they relate to each other's and establish a new culture different from the adulthood world.…”
Section: Types Of Icts and Using Patternsmentioning
confidence: 96%
“…''Street culture'' has been changed into ''room culture'' (Bacigalupe, 2011;Mesch, 2006b), where adolescents are isolated in their rooms playing and communicating with friends (Cardoso et al, 2008). The pattern of ICTs use seems to vary between email (Padilla-Walker, Coyne Cardoso et al, 2008;Ferguson, 2013;Ferguson, San Miguel, Garza, & Jerabeck, 2012;Lenhart et al, 2008;Sherry et al, 2006) and cell phone (Padilla-Walker et al, 2012;Wajcman, Rose, Brown, & Bittman, 2010). However, more than identify the pattern of the ICTs used by youth, is important to understand the context in which they are used (e.g., room alone, in mobility) and the interactions (e.g., contact with strangers, game with their offline partners, text messages to parents regarding difficult subjects) that they form in order to understand adolescents (Bacigalupe & Camara, 2011): how they construct their identity, how they relate to each other's and establish a new culture different from the adulthood world.…”
Section: Types Of Icts and Using Patternsmentioning
confidence: 96%
“…This is not necessarily detrimental, but could lead to a feeling that work never ends (Fender 2011;Mazmanian 2010;. A few studies, in contrast, depicted ICTs as facilitators of work-life balance (Quesenberry and Trauth 2005;Stoner et al 2009;Wajcman et al 2008Wajcman et al , 2010, assisting employees in fulfilling family responsibilities and thereby improving the management of work and family life (Currie and Eveline 2011;Golden 2013;Golden and Geisler 2007;Harmer et al 2008). Despite such potential benefits, ICT use extending work into non-work time is predominantly associated with work-life conflict, as conflicting roles create interpersonal tensions.…”
Section: Designated Non-work Time and Well-beingmentioning
confidence: 99%
“…In our third category, 13 papers focused on control over daily working hours (22,23,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)). An example question is: "To what extent are you able to influence the length of a work day, and the starting and ending times of a workday?".…”
Section: Categories Of Worktime Controlmentioning
confidence: 99%
“…Work-non-work balance Of the eight cross-sectional studies that examined the association between flextime and work-non-work balance, three (67,69,73) reported a significant positive association between flextime and work-non-work balance, whereas five studies (71,72,(74)(75)(76) reported no significant association. Together, these studies yielded a SIC (N=8) of 0.38 and provided moderately strong evidence for a positive association between flextime and work-non-work balance.…”
Section: Flextimementioning
confidence: 99%